TITLE: ESG-BASED MANAGEMENT MODEL FOR SUSTAINABLE TRANSFORMATION OF INDUSTRIAL ECOSYSTEMS: CASE OF BUKHARA OIL REFINERY (UZBEKISTAN) - Fatkulina I.S. (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article presents an original model of ESG-based (Environmental, Social, and Governance) management adapted for industrial ecosystems in transitional economies. Using the Bukhara Oil Refinery as a case study, the paper outlines the methodology, architecture, digital integration, and the results of a pilot implementation. The model combines international standards (GRI, ISO, TCFD), a step-by-step 4D transformation framework, project management tools (PMBOK, Agile), and digital analytics (Power BI, SAP). Preliminary results demonstrate the model’s economic, environmental, and institutional efficiency and its readiness for scaling across the national industry.